Infantile acne. - Saraswat, N.; Tripathy, D.M.; Kumar, S. (European Journal of Pediatric Dermatology, 2024)
We present a case of infantile acne vulgaris in a male child, age eighteen weeks, without any concomitant syndromic characteristics. After undergoing a thorough evaluation to identify any triggers and related anomalies, the patient received symptomatic treatment. The instance illustrates a prevalent dermatosis that only occurs in a rare age range.